2018
DOI: 10.1029/2018gl079802
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric Connection to the Abrupt End of the 2016/2017 Iberian Drought

Abstract: Southwestern Europe experienced extraordinary rainy and windy conditions in March 2018, leading to the end of the most severe drought since 1970 at continental scale. This anomalous weather was linked to a persistent negative North Atlantic Oscillation pattern. Two weeks earlier a sudden stratospheric warming (SSW) took place, preceded by the strongest planetary wave activity on record. In this study, we explore the connection between the SSW and the weather shift by employing a weather regime approach and flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 22 publications
3
49
0
Order By: Relevance
“…Ayarzagüena et al . () showed that there was a detectable downward Northern Annular Mode signal of this SSW to the troposphere in the reanalysis data.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Ayarzagüena et al . () showed that there was a detectable downward Northern Annular Mode signal of this SSW to the troposphere in the reanalysis data.…”
Section: Introductionmentioning
confidence: 97%
“…While Ayarzagüena et al . () did not specifically focus on the cold spell itself, but rather on the extreme precipitation event in the Iberian Peninsula, they concluded that the cold spell was likely triggered by the SSW. Due to the similarity to the composite mean behaviour, the cold spell was also indicated purely based on statistical models (Cohen et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In some cases these SSW events and associated blocking have been linked with extreme cold temperatures and heavy snowfall in parts of Europe, such as the February 2018 cold spell dubbed “The Beast from the East” in the United Kingdom (e.g., BBC News, ). Additionally, drought‐breaking precipitation in the Iberian Peninsula was also linked with the February 2018 SSW event (Ayarzagüena, Barriopedro, et al, ).…”
Section: Introductionmentioning
confidence: 99%